Methods for recruiting and interviewing corporate staff - Makushkin, Sergey A. (Linguistics and Culture Review, 2021)
The relevance of this paper is conditioned by the fact that the Russian practice of sourcing and recruitment of personnel in recent years increasingly tends to the professional level of recruitment, absorbing Western practice and in many ways being guided by it. Also, modern personnel selection methods are increasingly used. The study covers in detail the stages of personnel selection in Russia. The main criteria characterizing the preferences of employers of different organizations in the field of recruiting and hiring personnel are indicated. The main purpose of the study is to investigate the most effective methods of selecting and interviewing potential personnel. In this study, several different methods were used: analysis of existing methods, generalization of them for distribution into stages, and so on. The study identified 5 stages of interviewing for the selection of qualified candidates. Different interviewing methods were compared. Modern methods for selection are considered and their main advantages are revealed. Thus, it can be stated that the specifics of hiring personnel today differs from the preceding methods. Still, the size of the company and its nature of business are of great importance.